Drivers of songbird productivity at a restored gravel pit: Influence of seasonal flooding and rainfall patterns and implications for habitat management - Harrison, Nancy; Whitehouse, Mick (Agriculture, ecosystems & environment, 2012)
► We used 18 years of systematic bird ringing data to evaluate the drivers of change in passerine productivity. ► Productivity in migrant warblers was positively related to winter floods. ► Productivity in resident species was related to patterns in rainfall and cold snaps in spring and summer. ► The avian community is shaped by patterns in habitat change influenced by climate, beyond the control of local management. The restoration of riparian sites following aggregate extraction frequently aims to expand the wetland habitat, and enhance the wetland wildlife community. However, aggregate extraction sites, typically on river flood plains, are subject to unpredictable flooding along with climate variability and other factors beyond the control of local management that may be equally important in determining the success or failure of a restoration project. Here we report on an 18-year study tracking songbird productivity and changes in the avian community following the restoration of a gravel pit on the flood plain of the River Great Ouse, Cambridgeshire. As part of the British Trust for Ornithology's Constant Effort Site ringing scheme, the productivity (ratio of young: adult captured) of 5 migrant and 6 resident species was measured systematically. Capture data along with environmental variables pertinent to the flood plain habitat were analysed using generalised linear models. For some migrant species (e.g. willow warbler Phylloscopus trochilus and reed warbler Acrocephalus scirpaceus) breeding success was predicted by maximum winter flood. The productivity of resident species (e.g. dunnock Prunella modularis) was predicted not only by the overall amount of rain (positively related to production) but also the extent of spring downpours (negatively related to production). We expected that a major influence on the avian community would be the passage of time and associated vegetation succession. However, winter flood was found to be particularly important, as to a lesser extent was spring rain and unseasonal cold snaps. Detrended correspondence analysis of the total numbers of birds captured (adults+young) for 16 species showed that the changing avian community was shaped by winter floods more than by patterns in precipitation. It would appear that the avian community is influenced by patterns of habitat change, shaped as much by climate variability as local land management.